Effect of Training on Employee Performance with Work Motivation as Intervening Variable : (Study on Employees of PT Pertamina Fuel Terminal Tuban) - Andrian Ilham Bimantara; Bambang Widagdo; Marsudi Marsudi (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
The study aimed was to determine the effect of training on employee performance and to determine whether work motivation variables could mediate the influence of training on employee performance variables. This research was conducted on employees of PT Pertamina Fuel Terminal Tuban with a total of 58 respondents. Data was collected using a closed questionnaire. The data analysis technique used in this research is path analysis, hypothesis testing using t tet-test the Sobel test. The results of this study indicate that the training variable has a positive and significant effect on employee performance, the training variable has a positive and significant effect on work motivation and the work motivation variable has a positive and significant effect on employee performance.